Investigating extracellular vesicle communication in the endocrine cancers of the prostate and breast - Brown, Thomas J. (2024)
Introduction Across different cancer types, extracellular vesicles (EVs) have been shown to play a direct role in promoting the progression and metastasis of cancer cells. Furthermore, cancer derived EVs have been shown to enable crosstalk between cancer cells and other non-tumour cell types, aiding cancer progression. We hypothesise that EVs produced by endocrine-related cancers of the prostate and breast, mediate communication with stromal cells of distant tissues and the localised microenvironment to aid in cancer progression and metastasis. This hypothesis is explored through the three aims: 1) analyse the RNA cargos of EVs produced by bone metastatic prostate cancer cells to predict their potential effects; 2) determine the molecular effects of EVs produced by bone metastatic prostate cancer cell line PC3MLuc2a in vivo; and 3) investigate the effects of EVs produced by triple negative breast cancer cells on stromal mesenchymal cells to determine changes in chemoresistance and tumour cell growth.